The complete fairy tales of the Brothers Grimm - Grimm, Jacob, 1785-1863.; Grimm, Wilhelm, 1786-1859.; Zipes, Jack, 1937-; Gruelle, Johnny, 1880?-1938 (New York : Bantam Books, 2003)
A new translation of 239 fairy tales collected by the Brothers Grimm. Also includes a listing of their oral and/or literary sources.
"The inside illustrations by John B. Gruelle first appeared in Grimm's fairy tales, translated by Margaret Hunt in 1914"--T.p. verso.
English language and literature.
Keywords: Fairy tales -- Germany; Fairy tales; Folklore -- Germany